2020
DOI: 10.1177/1533033820963586
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NORAD as a Novel Predictor of Lymph Node Metastasis and Prognosis in Solid Tumors: A Systematic Review and Meta-Analysis

Abstract: Background: Non-coding RNA-activated by DNA damage (NORAD), a novel identified lncRNA, was found to be aberrantly expressed in various types of cancer. This meta-analysis was performed to evaluate the value of lncRNA NORAD as a prognostic biomarker in human cancers. Methods: We searched PubMed, Web of Science, PMC, and Embase databases thoroughly for eligible literatures. Studies which explored the relationship of lncRNA NORAD expression with clinical outcomes in human cancers were included in our meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The prognostic value of NORAD in human diseases was reported in previous investigations. A meta-analysis reviewed the association between NORAD and clinical outcomes of various cancer patients, and found that high NORAD levels related to a positive lymph node metastasis status and unfavorable survival of patients, which concluded NORAD a valuable prognostic biomarker of human cancers [26]. Downregulation of NORAD in neuroblastoma was demonstrated to predict patients' poor prognosis and advanced tumor stage [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of NORAD in human diseases was reported in previous investigations. A meta-analysis reviewed the association between NORAD and clinical outcomes of various cancer patients, and found that high NORAD levels related to a positive lymph node metastasis status and unfavorable survival of patients, which concluded NORAD a valuable prognostic biomarker of human cancers [26]. Downregulation of NORAD in neuroblastoma was demonstrated to predict patients' poor prognosis and advanced tumor stage [27].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs such as MALAT1, XIST and NORAD have been proven to be biomarkers for human tumor prognosis [47][48][49]. Also, some studies have shown that HULC expression is dysregulated in digestive system tumors [37,39,50].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in surgical practice, they could help in predicting lymph node burden and, therefore, avoid extensive axillary surgery in patients eligible for genomic tests [ 151 ], as it has been done recently with epigenetic signatures [ 152 ]. They could also work as biomarkers to predict objective response rates (ORR) to specific therapies in the neoadjuvant setting so tumor downstaging could be more precisely inferred [ 153 ].…”
Section: The Current Use Of Lncrnas As Clinical Biomarkers In Clinica...mentioning
confidence: 99%